The State of Practice in Requirements Engineering in the Development of Mobile Applications - Kelm, Wolleson Kevin; Mello, Aline Viera; Bernardino, Maicon (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
The quantity of software applications related to mobile devices is a growing trend, as well as the resources and the computer power offered by these kind of devices. Though some techniques of software engineering can be applied to this domain, these applications have to deal with a lot of limitations inherent to the mobile ecosystem that are not present in conventional desktop applications. One of the areas with the biggest importance, both in the traditional software engineering and on the one applied to mobile devices, is the Requirements Engineering. In this context, the general goal of this work is to identify the state of practice in requirements engineering used in the market for developing mobile applications. To achieve this goal, a survey was prepared and applied to mobile developers available on Google Play, obtaining 85 responses from 26 different countries. The results show that the time devoted to the Requirements Engineering is lower than recommended in the literature; less than half of survey participants performing the requirements validation activity and few developers make use of approaches to analyse software requirements. Therefore, Requirements Engineering is neglected in many aspects by most mobile application developers.